Peran Marketing Mix 3P (People, Process, Phisycal Evidence) dalam Keputusan Orangtua Memilih Man 2 Kuningan - Nurul Hidayati (Eduvis : Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to: (1) Describe the role of the 3p marketing mix (people, process, physical evidence) in MAN 2 Kuningan, (2) Explain the supporting factors and inhibiting factors for the 3p marketing mix (people, process, physical evidence) in the decision of parents to choose MAN 2 Kuningan, and (3) prove the efforts of MAN 2 Kuningan to overcome the inhibiting factors in the role of marketing mix 3p (people, process, physical evidence) in the decision of parents to choose MAN 2 Kuningan. This research is a qualitative research. Data collection was carried out through interviews, observation and documentation. The subjects of this study were the head of madrasah, educators, educational staff, and parents of students at MAN 2 Kuningan. The data analysis technique used is the Miles and Huberman model which consists of data reduction, data presentation, and conclusion. The results showed that in general the role of the 3p marketing mix (people, process, physical evidence) in MAN 2 Kuningan was good. However, there are some things that need to be improved. The results of this research can be concluded that: (1) the concept of marketing mix 3p (people, process, physical evidence) in MAN 2 Kuningan is good. But in practice, the selection of new students who are part of the process has not been optimal, the teaching and learning activities are not conducive to learning hours that are too dense, the madrasah website which is a publication media is not up to date, (2) supporting factors in the role of the 3p marketing mix (people, process , physical evidence) in MAN 2 Kuningan is the loyalty and cohesiveness of educators and education personnel. While the inhibiting factors are too dense learning hours, not maximal PPDB activities, and the madrasah website is not up to date, and (3) the efforts of the madrasah principal in dealing with overcrowded study hours are to motivate educators to be more creative and innovative, the efforts of the madrasah head In dealing with PPDB that has not been maximized is evaluating the readiness of schools in facilitating all activities related to PPDB in the emergency period, and the efforts of the head of madrasah in handling madrasah websites that have not been maximally used is to appoint a special person in charge related to madrasah social media management including website pages. Abstrak Penelitian ini bertujuan untuk: (1) Mendeskripsikan peran marketing mix 3p (people, process, phisycal evidence) di MAN 2 Kuningan, (2) Menjelaskan faktor pendukung dan faktor penghambat marketing mix 3p (people, process, phisycal evidende) dalam keputusan orangtua memilih MAN 2 Kuningan, dan (3) Membuktikan upaya MAN 2 Kuningan menanggulangi faktor penghambat dalam peran marketing mix 3p (people, process, phisycal evidence) dalam keputusan orangtua memilih MAN 2 Kuningan. Penelitian ini merupakan penelitian kualitatif. Pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Subjek penelitian ini yaitu kepala madrasah, pendidik, tenaga kependidikan, dan orangtua siswa di MAN 2 Kuningan. Teknik analisis data yang digunakan yaitu model Miles dan Huberman yang terdiri atas reduksi data, penyajian data, dan kesimpulan. Hasil penelitian didapatkan bahwa secara umum peran marketing mix 3p (people, process, phisycal evidence) di MAN 2 Kuningan sudah baik. Namun ada beberapa hal yang perlu diperbaiki. Hasil penelitian dapat disimpulkan bahwa: (1) konsep marketing mix 3p (people, process, phisycal evidence) di MAN 2 Kuningan sudah baik baik. Namun pada pelaksanaannya, seleksi siswa baru yang merupakan bagian dari proses belum maksimal, KBM kurang kondusif dengan jam belajar yang terlalu padat, website madrasah yang merupakan media publikasi tidak up to date, (2) faktor pendukung dalam peran marketing mix 3p (people, process, phisycal evidence) di MAN 2 Kuningan adalah loyalitas dan kekompakan pendidik dan tenaga kependidikan. Sedangkan faktor penghambatnya adalah jam belajar terlalu padat, belum maksimalnya kegiatan PPDB, dan website madrasah tidak up to date, dan (3) upaya dari kepala madrasah dalam menangani jam belajar yang terlalu padat adalah memotivasi tenaga pendidik untuk lebih kreatif dan inovatif, upaya kepala madrasah dalam menangani PPDB yang belum maksimal adalah mengevaluasi kesiapan sekolah dalam memfasilitasi semua kegiatan yang berhubungan dengan PPDB dimasa darurat, dan upaya kepala madrasah dalam menangani website madrasah yang belum maksimal penggunaanya adalah menunjuk penanggung jawab khusus terkait dengan pengelolaan media sosial madrasah termasuk laman website.